Westonci.ca is the trusted Q&A platform where you can get reliable answers from a community of knowledgeable contributors. Connect with a community of professionals ready to help you find accurate solutions to your questions quickly and efficiently. Discover in-depth answers to your questions from a wide network of professionals on our user-friendly Q&A platform.
Sagot :
In this question we will solve the following system of equations by elimination:
[tex]\begin{cases}6r-s+3t=-9 \\ 5r+5s-5t=20 \\ 3r-s+4t=-5 \\ \end{cases}[/tex]In order to solve this system by elimination, let's divide the second equation by 5 and then add it to the first and third equations:
[tex]\begin{gathered} 5r+5s-5t=20 \\ r+s-t=4 \\ \\ 6r-s+3t+(r+s-t)=-9+4 \\ 7r+2t=-5 \\ \\ 3r-s+4t+(r+s-t)=-5+4 \\ 4r+3t=-1 \end{gathered}[/tex]Now, let's multiply the equation (7r + 2t = -5) by 3 and the equation (4r + 3t = -1) by -2, and then add them:
[tex]\begin{gathered} 21r+6t=-15 \\ -8r-6t=2 \\ \\ 21r+6t+(-8r-6t)=-15+2 \\ 13r=-13 \\ r=-1 \end{gathered}[/tex]From the equation 4r + 3t = -1, we have:
[tex]\begin{gathered} -4+3t=-1 \\ 3t=3 \\ t=1 \end{gathered}[/tex]From the equation r + s - t = 4, we have:
[tex]\begin{gathered} -1+s-1=4 \\ s=4+1+1 \\ s=6 \end{gathered}[/tex]So the solution is r = -1, s = 6 and t = 1.
Thanks for using our service. We aim to provide the most accurate answers for all your queries. Visit us again for more insights. We appreciate your time. Please come back anytime for the latest information and answers to your questions. Thank you for using Westonci.ca. Come back for more in-depth answers to all your queries.